Potential and Growth of Several Types of Plants in the Absorption of Heavy Metal Lead (Pb) in the Media of Ex Tin Mining Soil in Siabu Village, Salo District, Kampar Regency - Darlis, Viny Volcherina; Putriani, Chirin Ni’mah; Yoza, Defri; Pebriandi, Pebriandi (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2023)
Tin mining activities in Siabu Village, Salo District, Kampar Regency, have environmental impacts, leading to soil pollution by heavy metals, particularly lead (Pb). This study aims to evaluate the potential and growth of five plant species (A. mangium, P. falcataria, S. macrophylla, I. cylindrica, and M. malabathricum) in phytoremediation of soil contaminated with lead from tin mining. The research employed a completely randomized design with five treatments and four replications, totaling 20 experimental units. Data were analyzed using SPSS 20.0, and if significant, further analysis was conducted using Duncan's New Multiple Range Test (DNMRT) at a 5% level of significance. The results of the research that had been conducted showed that the five types of plants had the potential to absorb the heavy metal lead (Pb) but with different absorption concentration levels. The highest absorption of lead (Pb) in the seedling group was P1 (A. mangium) treatment with the ability to absorb Pb metal at 6.33 ppm and the remaining Pb metal content in the soil of 14.18 ppm, while the absorption of heavy metal lead (Pb) which was highest in the lower vegetation group was treatment P5 (M. malabathricum) of 9.10 ppm with the remaining Pb metal content in the soil of 7.75 ppm. Keywords: Lead (Pb), Pollution, Phytoremediation, Heavy metals